2012
DOI: 10.1111/j.1750-3841.2011.02580.x
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Antimicrobial Activity of Nisin‐Loaded Liposomal Nanoparticles against Foodborne Pathogens

Abstract: This study was designed to evaluate the prolonged antimicrobial stability of nisin-loaded liposome (LipoN) nanoparticles against Listeria monocytogenes and Staphylococcus aureus. The sizes of bare liposomes and LipoN were uniformly distributed between 114 and 125 nm. The nanoparticles were homogeneously dispersed in water with less than 0.2 of polydispersity index. The zeta potential value of LipoN was +17.1 mV due to the positive charged nisin, attaining 70% of loading efficiency. The minimum inhibitory conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 29 publications
2
13
0
Order By: Relevance
“…In general, the main aim of the current study is to develop an efficient method for the loading of nisin onto mesoporous silica nanoparticles of various surface chemistries, so as to enhance the antimicrobial agent's stability under various conditions. The obtained results in the current study on the nisin when loaded on the nanoparticles are comparable to those reported in previous studies 17,[39][40][41] . The results obtained in those studies indicate that the loading of nisin onto nanoparticles such as chitosan/alginate 17 , liposomal 41 , solid lipid 40 and carbohydrate nanoparticles 39 improves its antibacterial activity and stability.…”
supporting
confidence: 92%
“…In general, the main aim of the current study is to develop an efficient method for the loading of nisin onto mesoporous silica nanoparticles of various surface chemistries, so as to enhance the antimicrobial agent's stability under various conditions. The obtained results in the current study on the nisin when loaded on the nanoparticles are comparable to those reported in previous studies 17,[39][40][41] . The results obtained in those studies indicate that the loading of nisin onto nanoparticles such as chitosan/alginate 17 , liposomal 41 , solid lipid 40 and carbohydrate nanoparticles 39 improves its antibacterial activity and stability.…”
supporting
confidence: 92%
“…Delivery of melittin resulted in more than 3 log reductions in the number of viable E. coli colonies within 60 min of incubation, with activity preserved despite repeated addition of bacterial cells due to the extended release of melittin from the PEG-stabilized lipid disks. Similarly, the encapsulation of nisin in liposomes composed of egg hydrogenated L-α-phosphatidylcholine/cholesterol (8:1, w/w) to form narrowly dispersed nisin-loaded liposomes (LipoNs) of 125 nm in diameter and + 17.1 mV zeta-potential was found to significantly enhance the stability and activity of the AMP in brain heart infusion agar against Listeria monocytogenes and S. aureus as compared to free nisin [154].…”
Section: Delivery Of Membrane-active Ampsmentioning
confidence: 97%
“…Nisin nanoparticles have been tested against L. monocytogenes and S. aureus with good results [302][303][304], as well as bacteriocin nanovesicles [210] or nanoparticles [208,209] against different pathogens. Zou et al [302] evaluated the prolonged antimicrobial stability of liposome nanoparticles loaded with nisin against L. monocytogenes and S. aureus. The MIC of the nanoparticles against both microorganisms was 320 UI/mL, reducing their populations by more than 6 log CFU/mL after 48 and 72 h of incubation, respectively.…”
Section: Nanoparticles and Nanovesiclesmentioning
confidence: 99%